RESPONS PERTUMBUHAN STUMP JATI (Tectona grandis L.f.) TERHADAP DOSIS DAN WAKTU APLIKASI PUPUK PHOSKA - Efendi Efendi (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
A field experiment was conducted to determine the growth responses of teak stump to NPK fertilizer that contains S nutrient. The stumps of teak were treated with Phoska fertilizer: 0, 5, 10, 15 g/plant and the fertilizer dosages were applied at 0, 5, 10, and 15 days after planting. The results of the study showed that stem diameter, stem height, and seedling height of the teak were significantly affected by the dosages and application times of Phoska fertilizer at 1, 2, 3, and 4 months after planting. The leaf numbers, leaf length, and leaf width responded significantly to Phoska fertilizer. This study found a significant interaction between the dosages and application times of Phoska fertilizer on seedling height and leaf length at one month old after planting; on stem height, seedling height, and leaf numbers at three month old; on stem diameter, stem height, seedling height, and leaf numbers at four month old after planting. The study revealed that the application of 10 g/plant Phoska applied at a planting day was the best treatment to enhance the growth of teak stump.